I'm having a bit of a brain fart here, the problem is that I need to change this:
2 / (1i*sqrt(3))
into this:
(1i*sqrt(3)) / 2
I know there's a basic maneuver to flip that division statement, but having trouble thinking of it. Best answer to first answerer that explains the basic steps to accomplish.
2 / (1i*sqrt(3))
into this:
(1i*sqrt(3)) / 2
I know there's a basic maneuver to flip that division statement, but having trouble thinking of it. Best answer to first answerer that explains the basic steps to accomplish.

Rationalize the denominator by multiplying by its conjugate; you must multiply the numerator by this also to form a fraction equivalent to the original:
2 / (1i*sqrt(3)) * (1+isqrt3)/(1+isqrt3) = 2*(1+isqrt3)/(1i*sqrt(3)(1+isqrt3) = 2*(1+isqrt3)/(1(isqrt3)^2) = 2*(1+isqrt3)/(1i^2sqrt9) = 2*(1+isqrt3)/(1(1*3)) = 2*(1+isqrt3)/(1+3) = 2*(1+isqrt3)/4 = (1+isqrt3)/2
is my answer.
Did you miscopy something?
2 / (1i*sqrt(3)) * (1+isqrt3)/(1+isqrt3) = 2*(1+isqrt3)/(1i*sqrt(3)(1+isqrt3) = 2*(1+isqrt3)/(1(isqrt3)^2) = 2*(1+isqrt3)/(1i^2sqrt9) = 2*(1+isqrt3)/(1(1*3)) = 2*(1+isqrt3)/(1+3) = 2*(1+isqrt3)/4 = (1+isqrt3)/2
is my answer.
Did you miscopy something?